Turkish version of the Junior Metacognitive Awareness Inventory: The validation study - (:unkn) unknown (My University, 2010)
This article describes a study measuring metacognition by means of the Junior Metacognitive Awareness Inventory developed in the USA which was then adapted to be used in Turkey. The survey data from 314 middle school students and 589 tenth grade students were collected in two phases to facilitate both the exploratory factor analysis (EFA) and the confirmatory factor analysis (CFA). Furthermore, the reliability analysis of the scores and convergent, discriminant, and subgroup validity coefficients were examined. Findings suggested that the inventory measures two constructs, namely, the knowledge and regulation of cognition. These results demonstrated that the Turkish version of Jr. MAI is a valid and reliable instrument which may serve as useful in guiding future research aiming to understanding students’ metacognitive awareness.

Bu çalışmanın iki amacı vardır. İlki, bilişüstü yeti boyutlarını belirlemek üzere Bilişüstü Yeti Envanteri’ni Türkçeye uyarlamak, ikincisi ise envanterin geçerlik ve güvenirliğini Türk kültüründe test etmektir. Bilişüstü yeti, bireylerin kendi öğrenme yapısını algılama ve kendi öğrenme özelliklerinin farkında olma gibi zihinsel güçlerini kapsamaktadır. Çalışma, farklı sınıf düzeylerinde 314 ilköğretim öğrencisinin bilişüstü yeti puanlarının yer aldığı açımlayıcı faktör analizi ve 589 onuncu sınıf öğrencisinin bilişüstü yeti puanlarının yer aldığı doğrulayıcı faktör analizi olmak üzere iki aşamadan oluşmaktadır. Öğrencilerin bilişüstü yeti puanlarının güvenirlik analizleri yapılmış ve uyuşum, ayırtedici ve altgrup geçerlikleri incelenmiştir. Bulgular, envanterin “Bilişin Bilgisi” ve “Bilişin Düzenlemesi” olmak üzere iki boyuttan oluştuğunu göstermektedir. Bu sonuçlar envanterin, öğrencilerin bilişüstü yetilerini ölçmede geçerli ve güvenilir bir araç olduğunu kanıtlamaktadır.
Bilişüstü Yetiler Envanteri'nin Türkçe'ye uyarlanması: Geçerlilik çalışması
Keywords: Eğitim, Eğitim Araştırmaları